Is the Middle Eocene Climatic Optimum (MECO) recorded in the central-western Tethys? - C. Agnini; D. J. Spofforth; E. Fornaciari; L. Giusberti; L. Lanci; V. Luciani; H. Pälike; D. Rio; G. Muttoni (2007)
We have established the carbonate content (%) and the stable oxygen and carbon isotope composition of the bulk carbonates in 535 samples from the Alano di Piave section, located in the Venetian southern Alps, NE Italy. The biomagnetostratigraphic data allow us to establish a sound chronology that indicates that the Alano section extends from the upper part of the Chron C18r (ca. 39.3 Ma) to the base of Chron C16r (ca. 36.5 Ma). Our records show a marked long-term and high-frequency variability. In particular, isotope reveal an interval of striking variability between 13.60 and 25.30 m levels, in which is comprehended a sapropel-like interval. Major and distinct shifts in both δ13C and δ18O records are present within this interval. Specifically, a negative shift in δ18O values (ca. 1.2-1.3 °) mirrors an articulated change in δ13C values. A rapid negative shift of the δ13C values of ca. 0.7-0.8 ° is followed by a pronounced positive shift in correspondence with the onset of the sapropel-like interval. This positive δ 13C excursion precedes a short-lived δ13C negative excursion that leads a second rapid δ13C increase. This prominent perturbation in the global carbon cycle terminates abruptly when the carbonate content, δ13C and δ18O values simultaneously return to more stable conditions, albeit the δ13C curve shows a post-event interval of instability around the "stable" condition beyond the termination of the event. This isotope excursion interval, here referred to as Chron C18r/C18n event, is well constrained in time occuring from the upper Chron C18r (ca. 40.3 Ma) to the upper Chron C18n.1r (ca. 39,6 Ma). Interestingly, this event correlates exactly with the positive ca. 0.6 ° δ13C positive excursion recorded by Jovane et al. (2007) in the Contessa Highway section. In agreement with Jovane et al. (2007), we correlate this positive δ13C excursion with the MECO event of Bohaty & Zachos (2003) in the Southern Ocean. These results suggest that the interval of time between 40.35 and 39.6 Ma is characterized by a ...